A DRP-1 dependent autophagy process facilitates rebuilding of the mitochondrial network and modulates adaptation capacity in response to acute heat stress during C. elegans development. Issue 9 (2nd September 2021) - Chen, Yanfang; Culetto, Emmanuel; Legouis, Renaud
ABSTRACT: Temperature variations induce stressful conditions that challenge the ability of organisms to maintain cell homeostasis. The intensity and duration of heat stress affect cell response very differently, ranging from a beneficial effect – hormesis – to necrotic cell death. There is a strong interplay between the cell response to heat shock and macroautophagy/autophagy, which is induced to cope with stress. Using Caenorhabditis elegans, we developed a new paradigm to study adaptation to acute non-lethal heat-stress (aHS) during development. We found that aHS results in transient fragmentation of mitochondria, decreased cellular respiration, and delayed development. Moreover, an active autophagy flux associated with mitophagy events is triggered in many tissues, enables the rebuilding of the mitochondrial network and modulates the adaptive plasticity of the development, showing that the autophagic response is protective for C. elegans . Using genetic and cellular approaches, we showed that mitochondria are a major site for autophagosome biogenesis in the epidermis, under both standard and heat-stress conditions. We determined that DRP-1 (Dynamin-Related Protein 1) involved in mitochondrial fission, is an important player for the autophagy process and the adaptation to aHS. Our study suggests that DRP-1 is involved in coordinating mitochondrial fission and autophagosome biogenesis during stress.